The techniques of monetary control: a review article - ROWAN, D. (PSL Quarterly Review, 2014)
The present article provides a critical review of J. Aschheim’s Techniques of Monetary Control (Baltimore, 1961). This work is primarily concerned with the problem of monetary “technique”, defined as that of making the best use of “proximate” instrument variables given some more or less definite set of objectives in terms of the “ultimate” instrument variables. According to the author, discussions of technique frequently imply acceptance of a particular monetary theory that is an implicit assumption that “technical” efficiency in monetary control is both a necessary and a sufficient condition for overall “economic” efficiency. However, it is argued that this is correct only if the implied monetary theory is quantitatively and qualitatively adequate. The author concludes that, although Aschheim’s study is clear, informative and thoughtfully stimulating, it does not constitute a convincing defence of monetary “orthodoxy”. JEL: E40, E51, E52